PENGEMBANGAN MEDIA PEMBELAJARAN MENGGUNAKAN ADOBE FLASH CS3 PROFESSIONAL PADA MATERI TRIGONOMETRI SISWA SMK KELAS XI - Fauziyah, Faridah; Setiawani, Susi; Fatahillah, Arif (Department of Mathematics Education , University of Jember, 2016)
Abstract. The result of this development research is a product development of learning media, quality tested through valid criteria, practical and effective. The production of learning media in this development research used software adobe flash cs3 professional and also could be presented by accessing a website named mediabelajar.hol.es on sine rules material, cosine rules, and the area of the triangle if two sides and one angle was known. This research was done with 10 stages adapted from Alessi and Trollip development model, that was (1) determining the needs and objectives of media development, (2) collecting references, (3) deepening material, (4) preliminary design, (5) designing and manufacturing flow charts, (6) designing and making media structure, (7) making Story Board media, (8) making a media by using Adobe flash CS3 Profesional, (9) make the supporting material that is website, as a place to put media that has been developed in order to be widely used, (10) evaluating and revising media. This activity of developing a learning media produced a learning media that fulfilled criteria such as valid, practical and effective. Valid was indicated from the validation stage. Validator gave final score of material validation was 87,5% and final score of media validation was 91,07%, because of that this media could be said valid media. Besides that, this media also had a practical value was 2.97 which can be included as quite practical category, and it had effectiveness value was 72.4% which was included as effective category. Keywords : learning media, adobe flash cs3 professional, trigonometry